Adiponectin deficiency induces mitochondrial dysfunction and promotes endothelial activation and pulmonary vascular injury. Issue 12 (4th October 2019) - Shah, Dilip; Torres, Claudio; Bhandari, Vineet
Abstract : Adiponectin (APN), an adipocyte‐derived adipokine, has been shown to limit lung injury originating from endothelial cell (EC) damage. Previously we reported that obese mice with low circulatory APN levels exhibited pulmonary vascular endothelial dysfunction. This study was designed to investigate the cellular and molecular mechanisms underlying the pulmonary endothelium‐dependent protective effects of APN. Our results demonstrated that in APN –/– mice, there was an inherent state of endothelium mitochondrial dysfunction that could contribute to endothelial activation and increased susceptibility to LPS‐induced acute lung injury (ALI). We noted that APN –/– mice showed decreased expression of mitochondrial biogenesis regulatory protein peroxisome proliferator‐activated receptor γ coactivator 1‐α (PGC‐1α) and its downstream proteins nuclear respiratory factor 1, transcription factor A, mitochondrial, and Sirtuin (Sirt)3 and Sirt1 expression in whole lungs and in freshly isolated lung ECs from these mice at baseline and subjected to LPS‐induced ALI. We further showed that treating APN _/_ mice with PGC‐1α activator pyrroloquinoline quinone enhances mitochondrial biogenesis and function in lung endothelium and attenuation of ALI. These results suggest that the pulmonary endothelium‐protective properties of APN are mediated, at least in part, by an enhancement of mitochondrial biogenesis through a mechanism involving PGC‐1α activation.—Shah, D., Torres, C., Bhandari, V. Adiponectin deficiency induces mitochondrial dysfunction and promotes endothelial activation and pulmonary vascular injury. FASEB J. 33, 13617‐13631 (2019). www.fasebj.org